Antimicrobial Assessment of Resins from Calophyllum Antillanum and Calophyllum Inophyllum. - Cuesta Rubio, Osmany (2015)
The Calophyllum genus is well-known for its antimicrobial and cytotoxic activities, and therefore, we analyzed these biological activities for resins of Calophyllum antillanum and Calophyllum inophyllum growing in Cuba. C. antillanum resins showed a potent activity against Plasmodium falciparum (IC50 = 0.3 ± 0.1 µg/mL), while its cytotoxicity against MRC-5 cells was much lower (IC50 = 21.6 ± 1.1 µg/mL). In contrary, the resin of C. inophyllum showed an unspecific activity. The presence of apetalic acid, isoapetalic acid, calolongic acid, pinetoric acid I, pinetoric acid II, isocalolongic acid, pinetoric acid III, and isopinetoric acid III in C. antillanum resins was also confirmed. These results demonstrated for the first time the potential activity of C. antillanum resins against P. falciparum. Copyright © 2015 John Wiley & Sons, Ltd.